A Study of Concrete Deterioration for Bridge Column in Nakhon Nayok Province and the Abrasion Test of Repairing Mortar and Experiment of Column Models - Tiracort, Chanaphan; Khamringae, Thanasit; Kadeetong, Pongsapuk; Sinthaworn, Suppachai (RMUTL Engineering Journal, 2022)
This project aimed to study the deterioration of concrete piers in bridge. The residual capacity of reinforced concrete deteriorated columns were studied through two selected deterioration types which are smooth surface deterioration and rough surface deterioration. The tested models of reinforced concrete column were generated as the short column specimen, 20x20x60 cm. The abrasion resistance of repairing mortars and the capacity of columns were experimented by Rotating-Cutter Method which is modified from ASTM C944. The result shows that the capacity of smooth surface deteriorated column decreases by 4.13% whereas that of rough surface deteriorated column decreases by 7.67%. The rough surface models were repaired by plastering mortar and apply sodium silicate on the surface. After plastering, strength of the repaired columns was increased by 12.34%. In addition, the repairing material shows that plastering mortar with sodium silicate demonstrates higher abrasion resistance 0.3% by weight than normal mortar, and compressive strength increases by 6.41%.